A class of their own : Black teachers in the segregated South - Fairclough, Adam (Belknap Press of Harvard University Press, 2007)
In this major undertaking, civil rights historian Adam Fairclough chronicles the odyssey of black teachers in the South from emancipation in 1865 to integration one hundred years later. A Class of Their Own is indispensable for understanding how blacks and whites interacted after the abolition of slavery, and how black communities coped with the challenges of freedom and oppression.